Trastornos alimenticios, ansiedad y depresión en una muestra de estudiantes de psicología de la Universidad de Costa Rica - Montenegro M., Esteban (2012)
This research seeks to determine the correlation between anxiety, depression and eating disorders in a sample of psychology students as well as see the impact of them. The sample consisted of 71 students, we used the BDI, DAI and the EAT-26. MANOVA analysis was performed, and Pearson correlations and analysis of Cronbach. Results. We found a significant effect of gender on the level of eating disorders and a significant correlation between eating disorders and anxiety. Similarly, women scored higher on eating disorders than men, which is supported by the literature on eating disorders.